Sustainable assessment of low viscous biofuel for compression ignition engine using wear debris analysis – Tribological investigation - Konareddy Harshavardhan Reddy; Nanthagopal Kasianantham (Case Studies in Thermal Engineering, 2024)
Lemon Peel oil is one of the ecologically friendly biofuels has many significant benefits for power generation applications. Lemon peel oil is extracted from left over rinds of lemon peel by applying steam distillation process. In the present work, long term durability study of compression ignition engines has been conducted using 10 % and 20 % low viscous biofuels with diesel. For 256 h long term durability investigation, wear debris, ferrography evaluation of lubricating oil samples and cylinder liner surface roughness analysis are conducted for these fuels operations. The results have revealed that higher metal wear concentrations are observed in the samples of lubricant oil with LPO20 compared with LPO10 and diesel. It is due to more oxidation of fuel and lubricant oil dilution while running the engine. Similarly, wear of the engine cylinder liner surface is also more when the engine is fuelled with LPO20 as compared to LPO10 and diesel. In addition, Ferrography results have shown a higher wear concentration of lubricant samples collected from the LPO20-operated engine compared with other used fuels. Finally, it is concluded that has poor engine life due to its low viscous nature and it could be improved by suitable reformulation for long term application.